JURIDICAL ANALYSIS OF MULTIPLE LAND OWNERSHIP DISPUTES IN INDONESIA - Rizaldi, M Zaki; Insan, Isep H (Fakultas Hukum, Universitas Islam Bandung, 2023)
This study reviews the legal regulations on land certificates and the resolution of multiple certificates. The research method used is legal analysis with a focus on Indonesian agrarian law. Key challenges include a lack of public understanding of registration rules and regulatory weaknesses, which trigger complex disputes. Solutions include the monitoring of land registration maps and the process of certificate transfer. Dispute resolution can be through deliberation, arbitration, or court. Further efforts from BPN are needed to ensure the validity of land data for fair and effective dispute resolution.